2020
DOI: 10.1002/admt.202000136
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturization of Artificial Lungs toward Portability

Abstract: Artificial lungs support patients undergoing open‐heart surgery, organ transplantation, and in serious lung injury by providing oxygenation support through an extracorporeal circuit. Some patients require partial support for durations of a few weeks or months even after the surgery. Therefore, a portable or wearable lung assist device which can be operated for several weeks with minimum maintenance would be ideal. Miniaturization of blood oxygenators, using microfluidic technology, is a promising avenue for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…The LAD with SOUs of 130 µm was still able to rescue the animal to nearly 90% systemic oxygenation levels under hypoxic conditions. This was expected as our previous studies [ 29,30,33,34 ] have shown that the oxygen transfer characteristics of an MBO with double‐sided blood channels was not strongly dependent on the height of the device, especially for a height of greater than 100 µm. The LAD with 130 µm channel height however had a lower blood flow rate (60–70 mL min −1 ) in the corresponding in vivo experiment (Figure S7d, Supporting Information).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The LAD with SOUs of 130 µm was still able to rescue the animal to nearly 90% systemic oxygenation levels under hypoxic conditions. This was expected as our previous studies [ 29,30,33,34 ] have shown that the oxygen transfer characteristics of an MBO with double‐sided blood channels was not strongly dependent on the height of the device, especially for a height of greater than 100 µm. The LAD with 130 µm channel height however had a lower blood flow rate (60–70 mL min −1 ) in the corresponding in vivo experiment (Figure S7d, Supporting Information).…”
Section: Resultssupporting
confidence: 76%
“…A numerical analysis of the pressure drop was conducted [ 30,33 ] to estimate the optimal height range for the blood vascular network to achieve a pumpless operation (Figure S7, Supporting Information). The flow analysis showed that channel height can be reduced to ≈130 µm below which the pressure drop would be significantly high that a pumpless operation may not be possible.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, further optimisation of engineered networks may help in realising the enormous application potential of microfluidics, additive manufacturing, and Murray materials. Similarly, optimised fluidic networks would benefit upscaling of emerging methods for catalysis (Yi et al 2022), carbon capture (Moore et al 2019), droplet and particle production (Holtze 2013;Yadavali, Jeong & Lee 2018), three-dimensional (3-D) printing of polymer foams (Visser et al 2019), artificial arterial networks (Kinstlinger & Miller 2016), and microfluidic blood oxygenation (Dabaghi et al 2020). The purpose of this paper is to provide optimisation tools that are suitable for a broad range of fluid rheologies and readily applicable by scientists and engineers who design fluidic networks.…”
Section: Introductionmentioning
confidence: 99%
“…2019), artificial arterial networks (Kinstlinger & Miller 2016), and microfluidic blood oxygenation (Dabaghi et al. 2020). The purpose of this paper is to provide optimisation tools that are suitable for a broad range of fluid rheologies and readily applicable by scientists and engineers who design fluidic networks.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where newborns are not transitioning perfectly to extrauterine life and have lung failure, the artificial placenta will allow physicians to just simply put the infants to a placenta‐like support. [ 1 ]…”
mentioning
confidence: 99%